1956
DOI: 10.1161/01.cir.13.4.489
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of the Effect of Intermittent Heparin Therapy on the Course of Human Coronary Atherosclerosis

Abstract: Heparin, 200 mg. subcutaneously, was administered twice weekly to a group of 105 patients with known previous myocardial infarction. A comparable control group of 117 individuals received saline placebos. Over a two-year period, there were 21 deaths due to cardiovascular disease in the placebo group, 4 cardiovascular deaths in the heparin group. The observed differences in deaths between the two groups is statistically significant, p < .01. The results indicate that heparin, in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

1957
1957
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 30 publications
0
25
1
Order By: Relevance
“…It is likely that the occurrence of deaths in the first month in the heparin group only was a chance finding because in other studies the mortality in patients, whether or not treated with anticoagulants, has generally tended to be high in the first month.4·5 There is no indication that hepa¬ rin altered the circumstances of death at any time during the 12 months ( Table 7). The design of the present trial differed in several respects from that reported by En¬ gelberg et al 1 The mean ages of our heparin-treated and control groups (56.1 and 56.6 years, respectively) were lower than those in Engelberg's trial (62.6 and 61.7 years). Although the survival rate follow¬ ing myocardial infarction is worse among older patients, Engelberg's control group, with an approximate annual mortality of 12%, fared better than our low-dose phen¬ procoumon-and heparin-treated groups.…”
Section: Resultscontrasting
confidence: 69%
“…It is likely that the occurrence of deaths in the first month in the heparin group only was a chance finding because in other studies the mortality in patients, whether or not treated with anticoagulants, has generally tended to be high in the first month.4·5 There is no indication that hepa¬ rin altered the circumstances of death at any time during the 12 months ( Table 7). The design of the present trial differed in several respects from that reported by En¬ gelberg et al 1 The mean ages of our heparin-treated and control groups (56.1 and 56.6 years, respectively) were lower than those in Engelberg's trial (62.6 and 61.7 years). Although the survival rate follow¬ ing myocardial infarction is worse among older patients, Engelberg's control group, with an approximate annual mortality of 12%, fared better than our low-dose phen¬ procoumon-and heparin-treated groups.…”
Section: Resultscontrasting
confidence: 69%
“…These heparin fractions differ in their interaction with physiologically important proteins such as antithrombin III (Rosenberg, 1977) and Factor Xa (Engelberg, 1984). Heparin also exhibits several other biological functions, and its beneficial use in the prophylaxis and therapy of atherosclerotic disease is well documented (Engelberg et al, 1965;Telford & Wilson, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…A 1956 randomized controlled study [6] found that low-dose heparin therapy resulted in an 80% reduction in the subsequent mortality of patients who had recovered from a prior acute myocardial infarction. Antithrombotic effects may have contributed to the results but probably were of minor importance as the dose of heparin was far below a fully anticoagulant one.…”
Section: Atherogenesismentioning
confidence: 99%
“…Their role in the atherosclerotic process has been reviewed [6,57]. FR contribute to atherogenesis in many ways and, via this effect, to the pathogenesis of AD.…”
Section: Reactive Oxygen Species/free Radicalsmentioning
confidence: 99%